ENHANCING SECURITY IN IoT PLATFORM USING SECURE AUTHENTICATION PROTOCOL (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years IoT is becoming the trending technology which is playing a major role inbusiness, health care, military applications. Wireless communications are highly vulnerableto security threats as anything connected to internet are prone to cyberattacks and place forhackers. Various challenges in IoT are causing security threats and not ensuring End-to-Endencryption during transmission of information. Currently most IoT devices use default logincredentials and not secured with better configurations and protocols which paves way forcyberattacks. Advanced security standards cannot be employed for all IoT devices. Thispaper proposed a secure authentication protocol for the IoT platform for ensuring securityamong IoT devices which keeps track of security threats. An evaluation of the proposedprotocol is presented which proves that the protocol is able to address various securitythreats.